2021
DOI: 10.1002/acm2.13164
|View full text |Cite
|
Sign up to set email alerts
|

How low can you go? A CBCT dose reduction study

Abstract: Purpose Cone beam computed tomography (CBCT) is often used for patient setup based solely on bony anatomy. The goal of this work was to evaluate whether CBCT dose can be lowered to the level of kV image pair doses when used for bony anatomy‐based IGRT without compromising positioning accuracy. Methods An anthropomorphic phantom was CT scanned in the head, head and neck, chest, and pelvis regions and setup on the linear accelerator couch with the isocenter near the planned location. Cone beam computed tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…Table 1 also indicates a general trend that when acquired projections were halved off, SNR and CNR values in reconstructed images declined by about 1/3, and SSIM values decreased about 10 %. The finding revealed in this patient-based study [24] is consistent with the phantom based study that CBCT dose can be significantly reduced by protocol optimization.…”
Section: Resultssupporting
confidence: 90%
“…Table 1 also indicates a general trend that when acquired projections were halved off, SNR and CNR values in reconstructed images declined by about 1/3, and SSIM values decreased about 10 %. The finding revealed in this patient-based study [24] is consistent with the phantom based study that CBCT dose can be significantly reduced by protocol optimization.…”
Section: Resultssupporting
confidence: 90%
“…Thirteen multiple‐choice questions were included in the survey. The questions were structured with reference to the previous similar survey study 10 with necessary modifications based on the current reports on CBCT usage in the orthodontic field 1,3,4,6–9,11,12,14,15 . The survey was validated through pilot feedback from two orthodontic faculty members.…”
Section: Methodsmentioning
confidence: 99%
“…This study indicated that, in North America, only 18.2% of programs used CBCT as a diagnostic tool for every patient. In the 10 years since that study was conducted, there has been updated research regarding advances in low‐dose protocols for CBCT usages, such as mAs reduction, use of partial rotations, reduced numbers of projections, and larger voxel size, which were able to decrease the amount of ionizing radiation to orthodontic patients without compromising the diagnostic integrity of the radiographs 11–13 . Thus, an update on the modern perspectives regarding CBCT usage in orthodontics is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The imaging dose accrued with MV imaging 18 or CBCT 19 has been a concern with image‐guided radiation therapy, in particular with pediatric cases. Several works have explored the use of region‐of‐interest (ROI) CBCT 20 , 21 and MV‐CT 22 and found possible dose reductions of 16%–90% and 15%–75% with ROI‐based CBCT and MV‐CT, respectively, when compared with full‐field imaging.…”
Section: Introductionmentioning
confidence: 99%